2006
DOI: 10.1007/bf03033332
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 agonists, bromocriptine and quinpirole, increase MPP+-induced toxicity in PC12 cells

Abstract: Dopaminergic cell loss in the mesencephalic substantia nigra is the hallmark of Parkinson's disease and may be associated with abnormal oxidative metabolic activity. However, the delicate balance underlying dopamine decline and oxidative stress is still a matter of debate. The aim of this study was to analyze the possible modulation of D2 agonists and antagonists on MPP+ (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridinium ion) -induced cellular death in differentiated and undifferentiated PC12 cells. Using colorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…In this study, we tested neuronal PC12 cells, a known, reliable and efficient paradigm for the investigation of oxidative stress and neuroprotection of DA neurons 25,42. After NGF administration, PC12 cells differentiate into the neuronal-like phenotype that secretes high DA levels and expresses TH, DAT, neurofilaments as well as ERα and ERβ 25,4346.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested neuronal PC12 cells, a known, reliable and efficient paradigm for the investigation of oxidative stress and neuroprotection of DA neurons 25,42. After NGF administration, PC12 cells differentiate into the neuronal-like phenotype that secretes high DA levels and expresses TH, DAT, neurofilaments as well as ERα and ERβ 25,4346.…”
Section: Discussionmentioning
confidence: 99%
“…While MPTP does not directly cause midbrain degeneration in vivo , the toxin efficiently crosses the blood brain barrier where it is metabolically transformed to MPP+, the destructive form of the toxin, by glia. Moreover, MPP+ is actively transported inside dopaminergic neurons via the dopamine active transporter (DAT) since treating cells with pharmacological inhibitors of DAT protects cells from MPP+-induced cell death [6366]. Mechanistically, MPP+ blocks oxidative phosphorylation at the level of complex I and increases the steady state levels of mitochondrial superoxide.…”
Section: Pd Toxins and Their Mechanisms Of Autophagymentioning
confidence: 99%
“…These studies revealed D2 receptor is necessary for anti-hyperPRL activity of FMD. PC12 cells from rat pheochromocytoma abundantly express D2 receptors and DAT [15,16]. FMD significantly increased the expression of D2 receptors and DAT in PC12 cells.…”
Section: Discussionmentioning
confidence: 92%